Implementation of Certification Policy at Madrasah Tsanawiyah Ma'had Al-Zaytun, Gantar, Indramayu District - Sepriati, Umi; Rosnidah, Ida; Nursahidin, Nursahidin (Department of Public Administration, 2023)
This research aims to analyze the implementation of teacher certification policies at Madrasah Tsanawiyah Ma'had Al-Zaytun. The approach used is qualitative with descriptive methods and data collection techniques carried out by triangulation. The results of the research show that implementers and teachers at Madrasah Tsanawiyah Ma'had Al-Zaytun have a clear understanding of certification policy standards, although the targets of this policy have not been fully achieved, as can be seen from the fact that there are still MTs teachers who have not been certified. In terms of resources, conditions are considered to be quite adequate, including communication between organizations that runs smoothly without obstacles. The characteristics of implementers show that they have competencies that support the implementation of certification policies, as well as carry out good supervision. The implementor's disposition also looks positive, with a good response and strong responsibility in implementing the teacher certification policy. Social and economic factors are recognized as supporting the implementation of certification. However, from a political perspective, there are impacts related to the delay in certification benefits, which are indicated to be related to criminal charges involving the leadership of Ma'had Al-Zaytun. Overall, this research concludes that the implementation of the teacher certification policy at Madrasah Tsanawiyah Ma'had Al-Zaytun faces several obstacles, but also shows progress in certain aspects. Improvement efforts and appropriate solutions need to be identified to increase the effectiveness of teacher certification policies in the future.